Progress and Trends in Magnesium‐Based Materials for Energy‐Storage Research: A Review. Issue 3 (17th October 2017) - Shao, Huaiyu; He, Liqing; Lin, Huaijun; Li, Hai‐Wen
Abstract: For the realization of a hydrogen economy, one enabling technology is hydrogen storage. Magnesium‐based materials (MBMs) are very promising candidates for hydrogen storage due to the large hydrogen capacity and low cost. Challenges in the development of magnesium‐based hydrogen‐storage materials for various applications, particularly for onboard storage, are poor kinetics and unsuitable thermodynamics. Herein, new methods and techniques adopted by the researchers in this field are reviewed, with a focus on how different techniques could affect the hydrogen‐storage properties of MBMs, including kinetics and thermodynamics. Based on current progress, research trends in MBMs for various applications are introduced. Classical work from some pioneers, important milestones, and the latest development for these possible applications are summarized and future prospects in these fields are discussed. Abstract : Holding onto hydrogen : Magnesium hydride may supply hydrogen with a very high energy density. A comprehensive review of classic strategies and leading techniques is provided. Development trends in magnesium‐based materials for various potential applications, including onboard hydrogen storage, hydrogen supply through hydrolysis, heat storage, and renewable‐energy storage, are also discussed.